Plasma Inflammatory Cytokines Are Elevated in ALS - Tortelli, Rosanna; Zecca, Chiara; Piccininni, Marco; Benmahamed, Sara; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Capozzo, Rosa; Battista, Petronilla; Logroscino, Giancarlo (Frontiers in Neurology, 2020)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease which leads to death in a median time of 2-3 years. Inflammation has been claimed important to the ALS pathogenesis but its role is still not well characterized. In the present study a panel of five cytokines (IL2, IL6, IL10, IFN-gamma and TNF-alpha) measured in plasma has been investigated in ALS. These biomarkers of inflammation were measured in a population-based cohort of 79 patients with ALS and 79 age and sex matched healthy controls using the Bioplex technology (Bio-Rad). All the five cytokines were significantly increased in plasma samples of patients compared to controls (p<.0001), with IL6 having the highest median concentration (10.11 pg/mL) in the ALS group. Furthermore, IL6 was the plasma cytokine with the highest discrimination ability between patients and controls according to the the Receiver Operating Characteristic (ROC) analysis (AUC=0.93). At a cut-off point of 5.71 pg/mL, it was able to classify patients and controls with 91% of sensitivity and 87% of specificity. In the ALS group plasma IL-6 concentration correlated with demographic (age: rs=0.25, p=0.025) and clinical (ALSFRSr at evaluation: rs=-0.32, p=0.007; MMT: rs=-0.33, p=0.004; progression: rs=0.29, p=0.0395) parameters. In line with previous studies, our results confirm that inflammatory cytokines are elevated in ALS, supporting a possible role of inflammation in disease mechanism and progression. However, the precise role of inflammation in ALS needs to be further investigate on larger samples and with more mechanistic studies.